Effect of Vehicular Stream Characteristics on Traffic Noise - Amjed J. Abed; Amjad H. Albayati; Yu Wang (Salehan Institute of Higher Education, 2022)
Human health can be negatively impacted by exposure to loud noise, which can harm the auditory system. Traffic noise is the leading cause of noise pollution. This paper studies the problem of noise pollution on the roads in Baghdad, Iraq. Due to the increase in vehicle numbers and road network modifications in Baghdad, noise levels became a serious topic to be studied. The aim of the paper was thus to study traffic noise levels and the effect of the traffic stream on noise levels and to formulate a prediction model that identified the guidelines used for designing or developing future roads in the city. Then, the noise levels were measured based on five variables: the functional classification of roads, traffic flow, vehicle speed, distance from the carriageway, and skid number. An analysis of traffic noise prediction was conducted using a simple linear regression model to accurately predict the equivalent sound levels. Finally, the findings have shown that the formulated prediction model gives acceptable prediction noise levels since the R2 is 88.83%. The results showed that the noise levels measured were 23.1% and 48.8% higher than the allowable noise levels limited by Iraqi standards during the daytime and nighttime, respectively. Further, studying the alternatives used to improve the performance of the environment on the existing roads in Baghdad can be considered as a future research direction. Doi: 10.28991/CEJ-2022-08-12-016 Full Text: PDF